Evaluation of vorticity forces in thermo-sensitive cavitating flow considering the local compressibility. (January 2021) - Shen, Tangjun; Li, Xiaojun; Li, Linmin; Wang, Zhengdong; Liu, Yaoyao
Abstract: The correlation between hydrodynamic forces and cavity evolution has been widely investigated but has not been deeply revealed. This study uses force element method to analyse the characteristics of force evolution along with cavitation around a NACA0015 hydrofoil. A modeling framework using the mixture two-phase flow model considering the energy convection and compressibility is proposed, to investigate the compressibility and thermal effects in the thermo-sensitive cavitating flow. Moreover, a force element method is applied for evaluating vorticity forces. The evolution of lift and drag coefficients under different cavitation numbers is mainly studied. Results indicate that, with increasing cavitation number, the time-averaged lift and drag coefficients firstly rise and then decline. However, the drag coefficient decline trend is greater than the lift coefficient. Combined with cavity evolution, the transient lift and drag evolution is analysed. Positive lift elements are mainly concentrates on the cavity surface and transport with cavity development, but the rupture of detached cavity and the pressure wave will inhibit the growth. The lift force reaches its peak when the cavity forms with the attached cavity that is completely detached from the hydrofoil surface, because of the volume of positive lift element reaches its maximum. Except for the shearing fracture of leading edge with the effect of fluid impact, the evolution of drag elements is similar to the lift. This studies shows that the force element method can well reveal the mechanism of force evolution due to the cavitation.